일반 병동 환자의 기관 내 삽관 관련 저혈압과 저산소혈증 예측 점수 도구 개발. - 김수지; 최혜란 (Journal of Korean Critical Care Nursing, 2026)
Purpose : This study aimed to develop predictive scoring systems for hypotension and hypoxemia during intubation in general ward patients. Methods : This retrospective study included 963 patients who underwent intubation in general wards between January 1, 2022, and December 31, 2024. Patients were randomly assigned to development set (n=776) and a validation set (n=187). Predictive factors were identified using multivariable logistic regression analysis, and scores were derived from the regression coefficients. Model performance was evaluated using the area under the receiver operating characteristic curve. Results : The hypotension scoring system included six variables: age ≥70 years, indication for intubation, absence of chronic liver disease, pre-intubation systolic blood pressure <130mmHg, Glasgow Coma Scale <8, and pH <7.35. The total score was 14 points, with a cutoff value of 7. The area under the receiver operating characteristic curve was 0.70 (95% CI=0.66--0.74) in the development set and 0.65 (95% CI=0.57--0.73) in the validation set. The hypoxemia scoring system included six variables: female sex, admission to a medical department, indication for intubation, body mass index ≥25kg/m², pre-intubation oxygen saturation <93%, and a PaO2/FiO2 ratio <150. The total score was 16 points, with a cutoff value of 9. The area under the receiver operating characteristic curve was 0.76 (95% CI=0.72--0.81) in the development set and 0.71 (95% CI=0.62--0.80) in the validation set. Conclusion : These predictive scoring systems may facilitate the early and objective identification of high-risk patients, quantify risk factors, standardize clinical decision- making, and guide preventive interventions before intubation in general wards.